Financial Mathematical Analysis in Applying Interest Rates, Installments, Amortization, Present and Future Values to Home Ownership Loans - Reynalda, Bagas; Barri, Safiq Rofiul (International Journal of Global Operations Research, 2024)
Home ownership credit has become a choice for many people to own a home, so that credit repayment runs smoothly, there needs to be an analysis from a financial perspective and a strategy for repayment. This paper aims to analyze and calculate the application of financial mathematical concepts in the context of home ownership credit. The main focus involves interest rates, installments, amortization, present and future value. Through a quantitative approach, we investigate the impact of changes in interest rates on monthly payments, explain the amortization mechanism, and evaluate the implications of payment policies on loan repayment times. The result is that by using the application of financial mathematics you can calculate monthly payments, analyze amortization, calculate present value and so on. So this paper can be useful for planning home ownership loans.